An exploration of song cycles for the baritone voice: "An die ferne Geliebte" (1816) by Ludwig van Beethoven, "Sei Romanze" (1838) by Giuseppe Verdi, "Don Quichotte à Dulcinée" (1932-1933) by Maurice Ravel, and "Let Us Garlands Bring" (1938-1942) by Gerald Finzi - Cyphert, Matthew Derek (Kansas State University, 2017)
This Master’s Report is an examination of four vocal song cycles for the baritone voice. Song cycles researched, interpreted, and performed include An die ferne Geliebte (1816) by Ludwig van Beethoven, Sei Romanze (1838) by Giuseppe Verdi, Don Quichotte à Dulcinée (1932-1933) by Maurice Ravel, and Let Us Garlands Bring (1938-1942) by Gerald Finzi. In this report you will find information on the history of vocal song cycles, biographical information about composers and poets/lyricists, compositional analysis, historical breakdowns of the musical periods, musical and poetic interpretations, original texts and English translations, pedagogical and performance practice insights, and never before published transpositions of “Non t’accostare all’urna,” “More, Elisa, lo stanco poeta,” and “Nell’orror di note oscura” from Giuseppe Verdi’s Sei Romanze (1838). Songs in this report are: “Auf dem Hügel sitz ich spähend,” “Wo die Berge so blau,” “Leichte Segler in den Höhen,” “Diese Wolken in den Höhen,” “Es kehret der Maien, es blühet die Au,” and “Nimm sie hin den diese Lieder” from An die ferne Geliebte by Ludwig an Beethoven. “Non t’accostare all’urna,” “More, Elisa, lo stanco poeta,” “In solitaria stanza,” and “Nell’orror di note oscura” from Sei Romanze by Giuseppe Verdi. “Chanson romanesque,” “Chanson épique,” and “Chanson à boire” from Don Quichotte à Dulcinée by Maurice Ravel. “Come away, come away, death,” “Who is Silvia?,” “Fear no more the heat o’ the sun,” “O Mistress Mine,” and “It was a lover and his lass” from Let Us Garlands Bring by Gerald Finzi. The graduate recital was presented in partial fulfillment of the requirements for the Master of Music degree in vocal performance on April 9th, 2017 in All Faiths Chapel on the campus of Kansas State University. The recital featured the talents of baritone Matthew D. Cyphert and pianist Mitchell S. Jerko.
Keywords: baritone voiceSongs; Song Cycle; An die ferne Geliebte by Ludwig van Beethoven; Sei Romanze by Giuseppe Verdi; Don Quixotte à Dulcinée by Maurice Ravel; Let Us Garlands Bring by Gerald Finzi